Radiation risk of incident colorectal cancer by anatomical site among atomic bomb survivors: 1958–2009. Issue 3 (3rd April 2019) - Sugiyama, Hiromi; Misumi, Munechika; Brenner, Alina; Grant, Eric J.; Sakata, Ritsu; Sadakane, Atsuko; Utada, Mai; Preston, Dale L.; Mabuchi, Kiyohiko; Ozasa, Kotaro
Abstract : Radiation effects on colorectal cancer rates, adjusted for smoking, alcohol intake and frequency of meat consumption and body mass index (BMI) by anatomical subsite (proximal colon, distal colon and rectum) were examined in a cohort of 105, 444 atomic bomb survivors. Poisson regression methods were used to describe radiation‐associated excess relative risks (ERR) and excess absolute rates (EAR) for the 1958–2009 period. There were 2, 960 first primary colorectal cancers including 894 proximal, 871 distal and 1, 046 rectal cancers. Smoking, alcohol intake and BMI were associated with subsite‐specific cancer background rates. Significant linear dose–responses were found for total colon (sex‐averaged ERR/Gy for 70 years old exposed at age 30 = 0.63, 95% confidence interval [CI]: 0.34; 0.98), proximal [ERR = 0.80, 95% CI: 0.32; 1.44] and distal colon cancers [ERR = 0.50, 95% CI: 0.04; 0.97], but not for rectal cancer [ERR = 0.023, 95% CI: −0.081; 0.13]. The ERRs for proximal and distal colon cancers were not significantly different ( p  = 0.41). The ERR decreased with attained age for total colon, but not for proximal colon cancer, and with calendar year for distal colon cancer. The ERRs and EARs did not vary by age at exposure, except for decreasing trend in EAR for proximal colon cancer. In conclusion, ionizing radiation is associated with increased risk of proximal and distal colon cancers. The ERR for proximal cancer persists over time, but that for distal colon cancer decreases. There continues to be no indication of radiation effects on rectal cancer incidence in this population. Abstract : What's new? Increasing radiation dose is associated with elevated colon cancer incidence among atomic bomb survivors. Questions remain, however, about differences in radiation‐related increases in risk by anatomical subsite, particularly the proximal and distal colon and the rectum. In this study, analyses of radiation and colorectal cancer risk for Japanese atomic bomb survivors in the Life Span Study cohort show that ionizing radiation is associated specifically with elevated risk of proximal and distal colon cancers. Adjustment for body mass index and lifestyle factors had little effect on radiation risk estimates. No association was found between radiation exposure and rectal cancer.